Injury surveillance in the World Football Tournaments 1998-2012 - Junge, A.; Dvorak, J. (British Journal of Sports Medicine, 2013)
Background: International sports bodies should protect the health of their athletes, and injury surveillance is an important pre-requisite for injury prevention. The Fédération International de Football Association (FIFA) has systematically surveyed all football injuries in their tournaments since 1998.